A new and possibly critically endangered species of casque-headed tree frog Aparasphenodon Miranda-Ribeiro, 1920 (Anura, Hylidae) from southeastern Brazil - de Assis, Clodoaldo Lopes; Santana, Diego José; Da Silva, Fabiano Aguiar; Quintela, Fernando Marques; Feio, Renato Neves (Zootaxa, 2013)
A new species of casque-headed tree frog of the genus Aparasphenodon is described from the municipality of Cataguases (21º20’S, 42º45’W; 288 m a.s.l.) in the Atlantic Rain Forest of Minas Gerais State, southeastern Brazil. Aparasphenodon pomba sp. nov. is characterized by medium size (males, snout-vent length, SVL 51.6–60.5 mm; females, SVL 58.7–62.1 mm); snout almost round in dorsal view; dorsum and limbs with cream-colored reticulation on dark-brown background; spots on ventral surface cream-colored; lips white; cream-colored dorsolateral stripe originating on the snout, crossing the upper eyelid and extending posteriorly to the axilla level; and red iris.